Analisis Efektivitas Pemutihan Pajak Kendaraan Bermotor Di Samsat Jakarta Pusat Sebagai Upaya Peningkatan Penerimaan Pajak Daerah Tahun 2021 - Tasya Kusumaningtyas; Khairur Raziqiin (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
During the covid-19 pandemic, motor vehicle tax revenues decreased due to decreased purchasing power. Therefore, the government provides a relief in the form of motor vehicle tax incentives with the implementation of bleaching motor vehicle tax as an effort to increase local revenue. This study aims to determine the effectiveness of bleaching as an effort to increase the original income of Central Jakarta in 2021. The research method used is qualitative with descriptive approach. Based on the results of research that has been carried out shows that the implementation of motor vehicle tax bleaching is running effectively, when compared to 2020, motor vehicle tax revenue in Central Jakarta has increased by Rp. 180,285,654,772.00 or 1.14%. This is due to the socialization of samsat officers in Central Jakarta continue to follow and supported by the motor vehicle tax incentives so as to increase local revenue.